2013
DOI: 10.3109/07380577.2013.783725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Occupation-Based Obesity Prevention Program for Children at Risk

Abstract: Since the prevalence of obesity-related medical conditions in children and adolescents has increased over the past several years obesity prevention has become a vital need for our society and a focus of our professional practice. The primary aim of this pilot study was to increase children's experiences with physical activity and healthy foods to promote self-efficacy related to a healthy lifestyle. Using a pre- and posttest design, the Healthy Choices for Me program was evaluated for its efficacy. Interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…After-school programs have the potential to reach millions of children, as academic programming may make it difficult to implement health programming during school hours (Afterschool Alliance, 2013; Amis, Wright, Dyson, Vardaman, & Ferry, 2012). For example, Lau, Stevens, and Jia (2013) found improvements in attitudes related to physical exercise and healthy eating, following a 12-week after-school obesity prevention program. Madsen et al (2009) showed that an after-school obesity prevention program improved student fitness and reduced obesity.…”
mentioning
confidence: 99%
“…After-school programs have the potential to reach millions of children, as academic programming may make it difficult to implement health programming during school hours (Afterschool Alliance, 2013; Amis, Wright, Dyson, Vardaman, & Ferry, 2012). For example, Lau, Stevens, and Jia (2013) found improvements in attitudes related to physical exercise and healthy eating, following a 12-week after-school obesity prevention program. Madsen et al (2009) showed that an after-school obesity prevention program improved student fitness and reduced obesity.…”
mentioning
confidence: 99%
“…Studies from the school/community sector do not automatically consider BMI with age and sex in their anthropometric measurement (e.g., BMI z-score, BMI percentile). Two studies do not consider anthropometric measurement in their outcomes 36,42 and two others consider only BMI (not for age and sex) 45,55 . Further considering the 34 studies with anthropometric measurements, 23 are based on a measurement related to BMI or abdominal circumferences (e.g., BMI score, waist circumference).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, some studies showed only effects on part of the population 21,29 , or "mixed effects" 19,37,52 . Of the 10 remaining studies, which did not clearly show an effect on BMI, 9 had, at least, a significant influence on health factors 32,36,39,40,42,45,50,53,54 (e.g., physical, psychological or nutritional ones). To illustrate, Smith et al 53 showed that "significant intervention effects were found for screen time (mean  SE: -30  10.08min/d; p=.03), sugar-sweetened beverage consumption (mean: -0.6  0.26 glass/d; P=.01)".…”
Section: Efficacymentioning
confidence: 96%
See 2 more Smart Citations